What irony and humour reveal about our thoughts: the example of Marcu Biancarelli, Michel Houellebecq, and Angelo Rinaldi - Laignier, Ferdinand (Romanica Olomucensia, 2019)
This paper focuses on the notions of irony and humour which articulate a multiple disturbing comic schema within the novels of Marcu Biancarelli, Michel Houellebecq, and Angelo Rinaldi. With their ironic verve and black humour, the narrators aspire to transcend their supposed mediocrity, their self-destructive impulses, their desire for renewal to soften a subversive and nihilistic character caused by a violent and real disappointing thought. However, if irony, humour, and sarcasm provide an echo to the derision of the real, they never remain a safe haven. In order to assert itself and to shake off the tight bridle of the real consumed by injustices and absurdities, the protagonists play with language, intent, and seriousness in order to betray a painful reality, to take the clock backwards, to make it falter, and to deconstruct it. The use of ironic, humorous, and sarcastic figures, which trivialize reality as much as they illuminate it, prompts writers to wonder whether the manifestation of the spirit is not going to occur to the detriment of the heart. The dialectic of the heart and spirit allows them to descend deeply into the apprehension of works. If irony and humour are psychological traits, they are also the result of disenchantment produced by a modernity that is severely understood by the three authors.
Keywords: dialectic of irony; black humour; derision of the real; disenchantment with the world; language games